2013
DOI: 10.1002/ceat.201300285
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Modeling of Methane Hydrate Formation in the Presence of Low‐Dosage Water‐Soluble Ionic Liquids

Abstract: The kinetic and thermodynamic effects of three typical low‐dosage imidazolium‐based ionic liquids (ILs) on methane hydrate formation and dissociation were investigated, considering the anion nature and subcooling and/or overpressure driving forces. Isochoric hydrate formation and dissociation data were obtained by the modified slow step‐heating method. ILs proved to have a dual effect on both formation and dissociation of methane hydrate including thermodynamic and kinetic inhibition. Kinetic modeling of metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Kim et al (2011) investigated the impact of ILs with pyrrolidinium-based cations on methane hydrate formation, and they observed both thermodynamic and kinetic inhibition effects of ILs. Nazari et al (2013) studied thermodynamic and kinetic effects of three ILs with imidazolium-based cations on methane hydrate formation. They also presented kinetic modeling of methane hydrate inhibition on the basis of IL nature and electrostatic intermolecular interactions between water and ILs (Nazari et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al (2011) investigated the impact of ILs with pyrrolidinium-based cations on methane hydrate formation, and they observed both thermodynamic and kinetic inhibition effects of ILs. Nazari et al (2013) studied thermodynamic and kinetic effects of three ILs with imidazolium-based cations on methane hydrate formation. They also presented kinetic modeling of methane hydrate inhibition on the basis of IL nature and electrostatic intermolecular interactions between water and ILs (Nazari et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nazari et al (2013) studied thermodynamic and kinetic effects of three ILs with imidazolium-based cations on methane hydrate formation. They also presented kinetic modeling of methane hydrate inhibition on the basis of IL nature and electrostatic intermolecular interactions between water and ILs (Nazari et al 2013). Kang et al (2013) applied a mixture of ILs and polymer inhibitors and observed a synergistic effect on methane hydrate inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Muhammad Saad Khan 1,2 properties of IL-hydrate system. Simulation of COSMO-RS in calculating fundamental properties paired with the correlation developed in this work could now serve as a prescreening tool of ILs inhibition ability.…”
Section: Author Detailsmentioning
confidence: 99%
“…Gas hydrates are icelike crystalline solid compounds that could form in the presence of water and gas under favorable thermodynamic temperature-pressure condition [1]. At low-temperature and high-pressure conditions, water molecules (host) will surround the gas molecules (guest) and encapsulate the gas in a hydrogenbonded solid lattice [2]. Depending on the gases trapped, different structures of gas hydrates can be formed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation